2018
DOI: 10.3389/fncir.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Functional Imaging of the Auditory Cortex in Behaving Mice: From Neural Networks to Single Spines

Abstract: In vivo two-photon Ca2+ imaging is a powerful tool for recording neuronal activities during perceptual tasks and has been increasingly applied to behaving animals for acute or chronic experiments. However, the auditory cortex is not easily accessible to imaging because of the abundant temporal muscles, arteries around the ears and their lateral locations. Here, we report a protocol for two-photon Ca2+ imaging in the auditory cortex of head-fixed behaving mice. By using a custom-made head fixation apparatus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 60 publications
(104 reference statements)
1
30
0
Order By: Relevance
“…One experimental session typically involved 40-100 stimulus events. The total amount of water consumed by an animal on the rig was sufficient to prevent dehydration, which was confirmed by the body weight control (<20% weight loss throughout all the experimental days) 27 .…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…One experimental session typically involved 40-100 stimulus events. The total amount of water consumed by an animal on the rig was sufficient to prevent dehydration, which was confirmed by the body weight control (<20% weight loss throughout all the experimental days) 27 .…”
Section: Methodssupporting
confidence: 53%
“…It has been known that training experiences could enhance the overall neuronal population responsiveness in the relevant sensory cortex 12 . Thus, we next performed a set of two-photon Ca 2+ imaging experiments using a genetically encoded Ca 2+ indicator, GCaMP6f 19,27 (Supplementary Methods, Supplementary Movie 4), in A1 L2/3 to analyse single-cell responsiveness throughout our auditory training. By using widefield fluorescence imaging ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next employed two-photon Ca 2+ imaging [23][24][25] to visualize live neuronal population activities during MIM application ( Fig. 2a, see also Supplemental Methods).…”
Section: Mainmentioning
confidence: 99%
“…Previous studies have reported that the activities of auditory cortical neurons are involved in auditory associative learning for mice 9,10,26 . We therefore tested whether and how MIM application in the auditory cortex might affect the learning course for a sound-licking associative learning task 24 (Fig. 3a).…”
Section: Mainmentioning
confidence: 99%